Superconductive and flexible antenna based on a tri-nanocomposite of graphene nanoplatelets, silver, and copper for wearable electronic devices - Al Gburi, Ahmed Jamal Abdullah; Mohd Radi, Nor Hadzfizah; Saeidi, Tale; Mohammed, Naba Jasim; Zakaria, Zahriladha; Das, Gouree Shankar; Buragohain, Akash; Ismail, Mohd Muzafar (Elsevier B.V., 2024)
Printed electronics, fueled by graphene’s conductivity and flexibility, are revolutionizing wearable technology, surpassing copper’s limitations in cost, signal quality, size, and environmental impact. Graphene-based inks are positioned to lead in this domain, offering cost-effective solutions directly applicable to materials such as textiles and paper. However, graphene encounters a primary drawback due to its lack of an energy band gap, constraining its potential applications in various electronic devices. In this study, we present a novel formulation of a superconductive, flexible leather graphene antenna utilizing a tri-nanocomposite structure of Graphene Nanoplatelet/Silver/Copper (GNP/Ag/Cu), covering a wideband bandwidth from 5.2 GHz to 8.5 GHz. The electrical conductivity of the GNP/Ag/Cu sample was assessed using the four-point probe method. With each additional layer, conductivity increased from 10.473 × 10 7 S/m to 40.218 × 10 7 S/m, demonstrating a direct correlation between conductivity and antenna gain. The study evaluates the efficacy of various thicknesses of conductive Graphene (GNP/Ag/Cu) ink on drill fabric. Safety assurance is provided through specific absorption rate (SAR) testing, indicating 0.84 W/kg per 10 g of tissue for an input power of 0.5 W, in compliance with ICNIRP standards for wearable device safety. Additionally, a morphological analysis of the antenna was conducted, showcasing its potential for efficient signal transmission in wearable electronic devices.